Nano-assisted delivery tools for plant genetic engineering: a review on recent developments - Kumar P.; Rajput V.D.; Singh A.K.; Agrawal S.; Das R.; Minkina T.; Shukla P.K.; Wong M.H.; Kaushik A.; Albukhaty S.; Tiwari K.N.; Mishra S.K. (My University, 2025)
Conventional approaches like Agrobacterium-mediated transformation, viral transduction, biolistic particle bombardment, and polyethylene glycol (PEG)-facilitated delivery methods have been optimized for transporting specific genes to various plant cells. These conventional approaches in genetically modified crops are dependent on several factors like plant types, cell types, and genotype requirements, as well as numerous disadvantages such as time-consuming, untargeted distribution of genes, and high cost of cultivation. Therefore, it is suggested to develop novel techniques for the transportation of genes in crop plants using tailored nanoparticles (NPs) of manipulative and controlled high-performance features synthesized using green and chemical routes. It is observed that site-specific delivery of genes exhibits high efficacy in species-independent circumstances which leads to an increased level of productivity. Therefore, to achieve these outcomes, NPs can be utilized as gene nano-carriers for excellent delivery inside crops (i.e., cotton, tobacco, rice, wheat, okra, and maize) for desired genetic engineering modifications. As outcomes, this review provides an outline of the conventional techniques and current application of numerous nano-enabled gene delivery needed for crop gene manipulation, the benefits, and drawbacks associated with state-of-the-art techniques, which serve as a roadmap for the possible applicability of nanomaterials in plant genomic engineering as well as crop improvement in the future. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.